Effectiveness and Isotherm Models of Lewatit Monoplus S-108 on Lithium Adsorption Process from Bledug Kuwu Brine with Continuous Flow - Miftakhur Rohmah; Ariyo Suharyanto; Latifa Hanum Lalasari; Johny Wahyuadi Soedarsono (Jurnal Kimia Sains dan Aplikasi, 2021)
Sorption of a series of alkali metals (Ca, Mg, Li, and K) from Bledug Kuwu’s Brine into Lewatit MonoPlus S-108 resins has been studied. Bledug Kuwu’s Brine comprised 15.11 ppm Li, 179.91 ppm K, 72.01 ppm Ca, and 29.76 ppm Mg. The adsorption was carried out by varying pH of brine (4, 6, 8, and 10) and contact time (1, 2, and 4 hours) with continuous flow in column test at room temperature. The result showed the quantity adsorbate in outer resin: K>Li>Ca>Mg in all conditions, which is 0.038–0.043 mmol/g lithium, 0.087–0.09 mmol/g potassium, 0.031–0.035 mmol/g calcium, and 0.023–0.024 mmol/g magnesium into outer resin surface. The selectivity factor to lithium followed Mg/Li > K/Li> Ca/Li in all conditions. Contact time variable provided high lithium separation after the adsorption process for 2–3 hours, while pH had little effect. FTIR results affirm that resin was changed at new peaks M-O-M at low wavenumber with polystyrene crosslinked-divinylbenzene matrix and contains the sulfonic type. The results obtained from ICP were fitted to isotherm models in ion exchange, as follows: Langmuir, Freundlich, Temkin, and Dubinin-Radushkevic models. The best model of lithium adsorption into Lewatit S-108 is represented by Freundlich and Temkin Model (R2 ≥ 0.82) with 1.0056 mg/g of adsorption capacity (Kf) and 64.885 J/mol of heat process of sorption.